An Analysis of Code-switching by El Barack on TikTok Video: Code-switching - Ita Rosita; Ari Fajria Novari; Nur Azmi Rohimajaya (Universitas Aisyah Pringsewu, 2025)
This research focused on analysis of types and functions of code switching used by El Barack in TikTok videos. Ten samples of TikTok videos from the @inijedar channel featuring El Barack, the writers applied poplack theory which functioned to categorize the types of code-switching, and Gumperz which functioned to explain what are function used by El Barack on TikTok video. This research also adopted descriptive-qualitative methods. Data collection was carried out using observation, documentation and checklists. This research focuses on speeches containing code switching produced by El Barack. The analysis showed that subjects A4 to A10 showed different types of code switching, whereas subjects A1 to A3 did not. Overall, this research identified 58 examples of types and functions of code-switching across ten videos. These findings highlight the prevalence and variations of code switching in social media content and its potential implications for communication and education.